Gerakan Religio-Kultural MTA Dakwah, Mobilisasi dan Tafsir- Tanding - Sunarwoto Sunarwoto (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2012)
This article investigates the role of Majelis Tafsir Al-Qur’an (MTA), a dakwah movement operating aminly in Central Java. MTA is known as the Muslim purist movement whose mission focuses on the purification of Islam by utilizing the slogan back to the Qur’an and Sunnah. Using the social movemenet theory, the author analyzes the extent to which MTA uses cultural dakwah or symbolic-cultural mobilization as its dakwah strategy in order to produce counter-interpretation towards the established and hegemonic interpretation of the Javanese culture. Cultural dakwah can mean a bolization process of Javanese symbols by ataching new meaning and interpretation to thos symbols. The author further argues that even though the MTA’s dakwah movement is mainly characterized by confontative attitudes, the MATA has also shown its acomodative character by introducing new new understanding and meaning of the existing cultural symbols. Keywords: Majelis Tafsir Al-Qur’an (MTA), Islamic dakwah movement, symbolic-cultural mobilization.